The relationship between the quality cultural values and the quality cultural environment in public secondary schools in the southeast region, Vietnam - Do, Dinh-Thai; Huynh, Van-Son; Thi Nguyen, Quoc-Minh; Nguyen, Quoc-Bao; Tran, Van-Trung; Vo, Thuy-Trang; Le Do, Uyen-Phuong (Frontiers in Education, 2025)
IntroductionQuality culture serves as a tool and method to foster quality spirit in individuals and quality culture in collectives, as well as a core tool and method to guide educational organizations in continuous quality improvement and the successful establishment of a Total Quality Management (TQM) model. The study aims to explore the relationship between quality cultural values and the quality culture environment in public secondary schools in the Southeastern region, specifically investigating the extent to which quality cultural values influence the quality culture environment.MethodsThe paper surveys and evaluates the impact level of quality cultural values (11 values) on the quality culture environment (05 environments) in public secondary schools in the Southeastern region of Vietnam.ResultsMultiple linear regression analysis results indicate that quality cultural values influence the quality culture environment by 51.2% to 53.3% in Ho Chi Minh City, 40.0% to 46.8% in Binh Duong Province, and 45.8% to 50.9% in Tay Ninh Province. Four (Responsibility, Consensus, Pioneering, and Action) values are identified as core values in public secondary schools in Ho Chi Minh City, while two (Responsibility and Creativity, innovation) values are considered core values in public secondary schools in Binh Duong Province.DiscussionThe findings highlight that responsibility consistently plays a central role across provinces, whereas other values exert differential effects depending on contextual conditions. These results suggest that quality culture in secondary schools is shaped not only by shared values but also by regional disparities in resources and institutional environments.